Universalità e singolarità storica della Rivoluzione d’ottobre: da Lenin a Gramsci ai nostri giorni - Quartim de Moraes, João (——— Materialismo Storico ——— Rivista di filosofia, storia e scienze umane, 2018)
The Marxian announcement of the imminent revolutionary conquest of power by the subaltern classes of the whole world has not occurred; however, it is not possible to understand the history of the second part of the Nineteenth and the entire Twentieth centuries without referring to the dynamics identified for the first time by the Communist Manifesto. It will be Lenin who gives effect to Marxism, bringing socialist revolution to completion in a country that was still largely agricultural and settling class struggles in capitalist countries to the national liberation struggles of countries subjected to Western colonialism. If the consequences of the October revolution will affect the liberal West itself, massively favoring the development of the Welfare State, the start of the neoliberal counter-revolution, inaugurated by Thatcher and Reagan, will coincide largely with the crisis of the political system founded by Lenin . Likewise, the end of the Soviet Union will coincide with the start of a dangerous phase of re-colonization, in which the nuclear horror of the Cold War will be followed by the daily horror of the imperialist wars disguised as humanitarianism. Keywords: Marx; Engels; Lenin; Dialectics; World History.